The Effect Of Innovative Work Behavior On Employee Performance At Rocky Plaza Hotel Padang - widya qinasih pulungan; Hijriyantomi Suyuthie; yofi Kurnia (Departemen Pariwisata Universitas Negeri Padang, 2026)
Employee performance is one of the key factors determining an organization’s success in provid-ing quality service, particularly in the highly competitive hospitality industry. One factor believed to influence improvements in employee performance is innovative work behavior. This study aims to analyze the effect of innovative work behavior on employee performance at the Rocky Plaza Hotel in Padang. The study employs a quantitative approach using the associative-causal method. The study population consisted of 89 permanent employees, and the entire population was sampled using a saturation sampling technique. Data collection was conducted via a questionnaire using a self-assessment method. Data analysis was performed using descriptive statistics, validity tests, reliability tests, simple linear regression analysis, t-tests, and the coefficient of determination with the aid of SPSS version 27. The results of the study indicate that innovative work behavior has a positive and significant effect on employee performance. Employees who possess the ability to create, develop, promote, and implement new ideas tend to demonstrate better work quality, productivity, timeliness, responsibility, and cooperation. The findings suggest that enhancing in-novative work behavior can serve as an effective strategy for improving employee performance in the hospitality industry.